32. EVALUATION OF INITIAL RESULTS OF LAPAROSCOPIC SURGERY FOR REPAIRING CESAREAN SCAR DEFECT IN INFERTILE PATIENTS AT NGHE AN FRIENDSHIP GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical, paraclinical characteristics, and evaluate the outcomes of laparoscopic surgery for cesarean scar defects.Subjects and Methods: This is a cross-sectional descriptive study with prospective data collection on 21 patients who underwent laparoscopic surgery for cesarean scar defects at the Reproductive Support Center – Nghệ An Friendship General Hospital from June 2022 to June 2023. The study investigated the clinical and paraclinical symptoms of the patients before and after surgery. Results: The average age of the patients was 34.48 ± 4.75 years, with 41.6% having been infertile for over 5 years. Symptoms before surgery included post-menstrual bleeding in 90.4%, mid-cycle bleeding in 19%, dysmenorrhea in 33.3%, and pelvic pain in 23.8%. After surgery, post-menstrual bleeding decreased to 19%, mid-cycle bleeding disappeared, dysmenorrhea reduced to 14.3%, and pelvic pain decreased to 9.5%. Before surgery, 100% of patients had a cesarean scar defect and uterine cavity fluid, with 52.4% having a retroverted uterus. 76.2% had a triangular-shaped defect, 61.9% had a type III defect, and the remaining myometrial thickness was 2.79±1.17mm. After surgery, 47.6% of patients still had a scar defect, 14.3% had uterine cavity fluid, 19% had a retroverted uterus, 38.1% had a triangular-shaped defect, 9.5% had a type III defect, and the remaining myometrial thickness was 5.07±1.29mm. There was a correlation between the degree of scar defect and menorrhagia symptoms (p
Keywords: Cesarean scar defect; Cesarean section; Secondary infertility